Optimization of Dispersions in GeO2-doped Photonic Crystal Fibers with Square Lattice - Thuy, Nguyen Thi (VNU Journal of Science: Mathematics - Physics; Vol 39 No 2DO - 10.25073/2588-1124/vnumap.4787, 2023)
Germanium doped photonic crystal fibers with differences in the layers' air hole diameters in the cladding are presented to obtain flat dispersion, small effective mode area, and low attenuation property for supercontinuum generation applications. The flatness and small value of the dispersion depend on the lattice geometry when the fibers have the same germanium doping concentration. The dispersion of the square lattice fibers is a flatter and smaller value at the pump wavelength than the circular lattice fibers. Square lattice fibers with Ʌ = 0.9 µm, d 1 / Ʌ = 0.4 and Ʌ = 1.0 µm, d 1 / Ʌ = 0.45 are proposed for supercontinuum generation which has anomalous and all-normal dispersion, respectively. Their small dispersion values of 0.449 ps /nm.km and −1.096 ps/nm.km are suitable for broad spectrum supercontinuum generation. The small effective mode area and low attenuation of the two fibers of 3.221 µm 2 , 2.361 µm 2 and 1.805×10 −7 dB/m, 1.322×10 −15 dB/m, respectively are favorable conditions for choosing a laser pump sources with low peak power. The proposed fibers can be new supercontinuum generation source replacing traditional glass core fibers.